Management and early outcomes of children with appendicitis in the UK and Ireland during the COVID-19 pandemic: a survey of surgeons and observational study. Issue 1 (22nd October 2020) - Bethell, George S; Rees, Clare M; Sutcliffe, Jonathan R; Hall, Nigel J
Abstract : Objectives: Acute appendicitis is the most common surgical condition in children. In the UK, appendicectomy is the most common treatment with non-operative management unusual. Due to concerns about the risk of SARS-CoV-2 transmission during surgical procedures, surgeons were advised to consider non-operative treatment and avoid laparoscopy where possible. This study aims to report management and outcomes, to date, of children with appendicitis in the UK and Ireland during the COVID-19 pandemic. Design: Survey of consultant surgeons who treat children with appendicitis that informed a prospective multicentre observational cohort study. Setting: Data were collected from centres in the UK and Ireland for cases admitted between 1 April and 31 May 2020 (first 2 months of the COVID-19 pandemic) at both general surgical and specialist paediatric surgical centres. Participants: The study cohort includes 838 children with a clinical and/or radiological diagnosis of acute appendicitis of which 527 (63%) were male. Main outcomes measured: Primary outcome was treatment strategy used for acute appendicitis. Other outcomes reported include change in treatment strategy over time, use of diagnostic imaging and important patient outcomes to 30 days following hospital admission. Results: From very early in the pandemic surgeons experienced a change in their management of children with appendicitis and almost all surgeons who responded to the survey anticipated further changes during the pandemic. Overall, 326/838 (39%) were initially treated non-operatively of whom 81/326 (25%) proceeded to appendicectomy within the initial hospital admission. Of cases treated initially surgically 243/512 (48%) were performed laparoscopically. Diagnostic imaging was used in 445/838 (53%) children. Cases treated non-operatively had a shorter hospital stay than those treated surgically but hospital readmissions within 30 days were similar between groups. In cases treated surgically the negative appendicectomy rate was 4.5%. There was a trend towards increased use of surgical treatment and from open to laparoscopic appendicectomy as the pandemic progressed. Conclusion: Non-operative treatment of appendicitis has been widely used for the first time in children in the UK and Ireland and is safe and effective in selected patients. Overall patient outcomes do not appear to have been adversely impacted by change in management during the pandemic thus far.